INFLUENCE OF WOVEN KENAF/POLYETHYLENE TEREPHTHALATE FIBER REINFORCED POL YOXYMETHYLENE HYBRID COMPOSITE ON MECHANICAL AND PHYSICAL PROPERTIES - , YAKUBU DAN-MALLAM (2014)
The challenges of using natural fibers in polymer composites include high moisture uptake and poor interfacial bonding with thermoplastic matrix. In this study, the influence of woven kenaf/polyethylene terephthalate (PET) fiber reinforced polyoxymethylene (POM) hybrid composite was investigated to address the challenges of high moisture uptake and balanced mechanical properties. Short, continuous and woven fiber composites and their hybrids, were produced by compression molding. Mechanical properties and water absorption test were carried out according to their respective ASTM standards. Tensile strength of 35.2 MPa was obtained for short fiber POM/kenaf (80/20) composite while 41.3 MPa was obtained for the hybrid composite (POM/kenaf/PET).